Offshore compliant platforms : analysis, design and experimental studies - Chandrasekaran, Srinivasan; Nagavinothini, R., 1991- (Wiley-ASME Press series., 2020)
"Offshore Compliant Platforms: Analysis, Design and Experimental Studies covers the analysis and design of compliant offshore structures with a focus on new generation platforms like triceratops, Buoyant Leg Storage and Regasification platforms. While the conceptual development of conventional platforms are presented briefly, detailed description of the design and development of the new generation platforms discussed in this book are highly novel and still in the preliminary stages of study in the existing literature. Offshore Compliant Platforms: Analysis, Design and Experimental Studies describes the preliminary design of triceratops in ultra-deep waters and presents a detailed analysis of environmental loads which are inherent in offshore locations such as wave, wind and current. The new methodology for the dynamic analysis of triceratops under ice loads, predominantly in ice-covered regions is also discussed with detailed parametric studies. Also covered is the structural geometry and the different methods of analysis for assessing the performance of any other similar offshore platform under the special loads. The discussion on the fatigue analysis and service life prediction will also be useful during the preliminary and detailed design stage of an offshore platform"--